Relasi agama dengan kekerasan dan konflik - Syarifah, Hasnia Imroatis (Maliki Interdisciplinary Journal, 2024)
There are so many cases of conflict and violence in the name of religion. In fact, many conclude religion as a source of conflict. Even though religion never justifies the existence of conflict and violence in it. All religions prohibit gentleness, serenity, and harmony. The article he wrote aims to explain that religion is not a source of conflict and how to minimize religious conflict that occurs in society. One of the factors causing the conflict is truth claim, where he feels he and his religion are the most correct blames others. Behind the case of religious conflict, there are many factors that must be known first. So far, religion has only been used as an excuse to cover up real problems. In fact, the key in the relationship between conflict and religion that occurs is human beings. Therefore, humans must minimize religious conflict by respecting, appreciating, and tolerant.